PEMBERDAYAAN WARUNG NASI BU SUSI MELALUI INOVASI PENGEMBANGAN PASAR DAN PEMASARAN BUMBU SAMBAL PECEL - Jumati, Nurleila; Muliatie, Yurilla Endah; Ardliyanti, Arif; Aulia, Anas Tasya; Fatmawati, Annisa Eka (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
The purpose of the program is to increase the capacity of Warung Nasi Bu Susi MSME actors through product derivative innovations as well as market and digital marketing strategies. Warung Nasi Bu Susi's business, which was pioneered in 2017, experienced a significant decrease in turnover after moving its location into a village area, so consumer access became limited. One of the potential opportunities that can develop is pecel chili sauce, but it has not been marketed professionally. The main problems of partners include three aspects, namely: (1) production that does not have standards and packaging, (2) marketing that is still conventional, has not made optimal use of digital media, and (3) limited business legality, including the absence of halal certification. The program implementation method is designed in a participatory, adaptive manner in a collaborative atmosphere, with stages including socialization, business mentoring and coaching, product innovation and packaging design training, introduction to digital marketing, sales and branding simulation, to assistance in managing business legality. The results of the activity show an increase in the capacity of partners in developing ready-to-sell chili sauce derivative products with packaging power, brand identity, and digital marketing strategies. Partners obtain the development of business legality, in the form of expanding NIB (Entrepreneurial Identification Number) and halal certification so that there is an increase in the market outside Keboan Hamlet and outside the city that is oriented towards business sustainability. Partners have also experienced an increase in the marketing turnover of sambel pecel from non-existent to 30%.